Gender and sexuality issues in the training course of scholarships of the pedagogical residence program in the area of natural sciences and their technologies (Revista Contexto & Educação, 2025)
As part of the formation of subjects, aspects that involve the constitution of men and women are present in all social contexts. Issues of gender and sexuality permeate school content in biological, social, and cultural aspects. Evidence shows that generally, the curriculum of undergraduate courses in Brazil does not present specific subjects or content that address issues of gender and sexuality at the undergraduate level. This can lead to a lack of preparation for planning activities regarding the approach to this topic, as well as a lack of social interest in the importance of taking these issues to the classroom. The present investigation aimed to analyze teaching plans prepared by undergraduate students in the area of ​​Natural Sciences and its Technologies, on the topic of gender and sexuality. The material produced was analyzed using Content Analysis. The results indicate some misunderstandings regarding the terms and methodologies for working with this theme since limited creativity is visible regarding the possibilities of resources and teaching strategies.
Keywords: teacher training; pedagogical practices; inclusion